Given f(x)=2x^2+8 and g(x)=5x -6
please solve this
(2x^2+8)+(5x -6 )
What do I do do I multiply 2x and 5x?
no. 2x^2 and 5x ar not lik terms because they do not have same power of x
Do I need a graphing calculator to solve this?
now the answer will be \[ 2x^2+ 5x +2\]
(f+g)(x)= f(x)+g(x) = 2x^2 +8 + 5x-6 = 2x^2+ 8 +1
Oh. . . How confusing it shows it this way in the book.
2x^2+ 8 +1 is very wrong
Ahh. . . Okay then. I will follow your lead, what's next?
i have given the answer to that
Oh okay. I will try the second one on my own you tell me if it's correct.
\[(2x^2+8)(5x -6 ) =\]
\[2x^2*5x -2x^2*6 +5x*8-8*6\]
that would be the answer